Statins Against Drug-Induced Nephrotoxicity - Simin Dashti-Khavidaki; Azadeh Moghaddas; Behrooz Heydari; Hossein Khalili; Mahboob lessan-Pezeshki; Mahbooh Lessan-Pezeshki (Frontiers Media S.A., 2013)
Drug-induced nephrotoxicity (DIN) accounts for up to 60% of hospital acquired acute kidney injury with considerable morbidity and mortality. Several efforts have been made to reduce drug-induced nephrotoxicity; however, DIN remains a matter of concern. Statins with their antioxidant, anti-inflammatory and anti-apoptotic effects may have the potential to protect kidney against DIN. The present review evaluated all of the available in vitro and in vivo studies that examined the use of statins as renoprotective agents against nephrotoxic drugs. Materials for this review were obtained by searching Medline, PubMed, Scopus, Cochrane central register of controlled trials, and Cochrane database of systematic reviews. Key words used as search terms included "statin", "3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors, "HMG-CoA reductase inhibitors", "nephroprotective", "renoprotective", "drug-induced renal diseases", "drug-induced nephrotoxicity", "drug-induced renal toxicity", "drug-induced nephropathy", "drug-induced renal side effects", and "contrast-induced nephropathy". This search was performed without time limitation. Only English language articles were included in this review. This review concluded that chronic statin user may be less prone to contrast-induced nephropathy (CIN) compared with statin non-users. Short-term high dose statin administration may also reduce the incidence of CIN in statin naïve patients. This renoprotective effect of statins against CIN is seen in low risk patients with normal kidney function or mild kidney dysfunction, but probably not in patients with moderate to severe renal dysfunction.  Based on available animal data, statins may protect kidney against gentamicin-, cisplatin- and cyclosporine-induced nephrotoxicity, however, theses animal results have not yet been confirmed by human data.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.